2017
DOI: 10.1002/cncy.21884
|View full text |Cite
|
Sign up to set email alerts
|

The role of thyroid FNA cytology in pediatric malignant lesions: An overview of the literature

Abstract: When one is dealing with pediatric thyroid lesions, fine-needle aspiration is the first diagnostic tool for the correct characterization of these nodules. Despite the apparent infrequency of thyroid cancers in children, recent data from the National Cancer Institute prove that the incidence has been increasing, especially in adolescents. With the same data, a higher prevalence of well-differentiated cancers can be estimated, with 90% diagnosed as papillary thyroid cancer. Nonetheless, some publications have de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 64 publications
(407 reference statements)
0
16
0
Order By: Relevance
“…The diagnostic role of FNAC in the evaluation of pediatric thyroid lesions has been thoroughly assessed and reported in the literature . In fact, numerous articles have emphasized that the majority of thyroid lesions are easily recognized and correctly diagnosed on cytological specimens.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The diagnostic role of FNAC in the evaluation of pediatric thyroid lesions has been thoroughly assessed and reported in the literature . In fact, numerous articles have emphasized that the majority of thyroid lesions are easily recognized and correctly diagnosed on cytological specimens.…”
Section: Discussionmentioning
confidence: 99%
“…The study was independently evaluated and approved by the institutional review boards of both institutions. All details regarding the LBC method and ancillary techniques have been described in our previous articles …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the 1st edition was published, several new variants of thyroid carcinoma have been described. The revised 2nd edition included a more detailed definition of the criteria for classifying some of the PTC variants and expanded the description of PTC variants to include solid, diffuse sclerosing, cribriform, and hobnail variants to improve their cytological identification . The 2nd edition also enriched the description of PDTC and ATC .…”
Section: Introductionmentioning
confidence: 99%
“…Although thyroid nodules are less common in children than adults, an overview of the literature has showed that pediatric thyroid nodules are more likely to be malignant and carry a 1.6‐fold higher cancer risk than that of adult population . The Management Guidelines for Children with Thyroid Nodules and Differentiated Thyroid Cancer from The American Thyroid Association recommends fine‐needle aspiration (FNA) as an essential tool for the assessment and management of pediatric thyroid nodules, and utilizing The Bethesda System for Reporting Thyroid Cytopathology (TBSRTC) as a guideline to categorize FNA cytologic findings .…”
Section: Introductionmentioning
confidence: 99%